Three-dimensional Volumetric Investigation of Onodi Cells: A Multi-slice Computed Tomography Study - Dieguez, Flavia Limberg (2023)
Introduction Onodi cells (OCs) are posterior ethmoid cells that are located above the sphenoid sinus, close to or even surrounding the carotid artery and optic nerve.Objective To investigate and evaluate the volumetric variation of OCs through multi-slice computed tomography (MSCT) scans.Methods We performed a retrospective review of MSCT scans of 79 subjects, 40 male and 39 female patients, Whose age ranged from 18 to 83 (mean: 39.6) years. The volumes of the OCs on the right and left sides were measured using the ITK-SNAP software (open-source) with semiautomatic segmentation. The possible relationships involving age, gender, contact with the optic nerve, extension of the pneumatization of the posterior ethmoid cells into the clinoid processes, mucous thickening in the anterior and posterior ethmoid cells, and obliteration of the sphenoethmoidal complex were analyzed with the Pearson correlation and Chi-squared tests according to the type of data compared and logistic regression models ( p < 0.05).Results We observed that an increase of one unit in the volume of OCs also increases the chance of extension of pneumatization into the clinoid processes by 0.15% ( p = 0.001). No significant correlations were identified regarding age, gender, and volume of the OCs.Conclusion The volume of the OCs has effects on the extension of pneumatization into the clinoid processes.